Pendekatan Ekologis untuk Keberlanjutan Pesisir: Integrasi Perlindungan Pantai, Vegetasi, dan Sistem Drainase Ramah Lingkungan - Qanitatul Isra Qamal; Dwi Gita Julianti; Akmanul Hakim; Anis Arsyta; Nikita Dara Tari (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Coastal areas are regions vulnerable to abrasion, developmental pressures, and climate change, thus requiring sustainable management approaches. This study aims to examine ecological approaches to support coastal sustainability through the integration of nature-based coastal protection, coastal vegetation management, and the implementation of environmentally friendly drainage systems. The method used is a qualitative descriptive study through literature review and analysis of the physical conditions of the coastal environment. The findings indicate that utilizing coastal vegetation as a natural barrier can reduce abrasion and improve environmental quality, while environmentally friendly drainage systems are effective in controlling waterlogging and enhancing water infiltration. The integration of these three aspects forms an adaptive, efficient, and sustainable coastal management system, which can serve as a reference for planning and developing coastal areas without compromising ecological balance.